Reviewed Work: Globalization and the Race to the Bottom in Developing Countries: Who Really Gets Hurt? by Nita Rudra (2008) - Muhammad Indrawan Jatmika (Global South Review, 2019)
Nita Rudra’s analysis in her book entitled Globalization and the Race to the Bottom in the Developing Countries challenges the argument of most globalization sceptics who argue that the bottom poor are the particular group who suffer the most from the globalization phenomenon.  Rudra’s main argument is that the domestic institutions will be the intermediate between global pressure and domestic social policy. As the aftermath, it is not the bottom poor of the citizens who hurts the most from the impact of the RTBs. It is precisely the middle class that hurts the most, because basically various kinds of policies such as government’s welfare distribution are controlled and determined by certain domestic institutions, whose access is controlled by the middle class and certain political groups, have been more oriented towards the interests of the middle class rather than than the interests of the bottom poor itself.